Radio in the digital age - Dubber, Andrew (Cambridge, UK. : Polity Press, 2013)
Radio's influence can be found in almost every corner of new media. This book assesses a medium that has not only survived the challenges of a new technological age but indeed has extended its reach.
Includes bibliographical references and index.
Keywords: Radio; Radio broadcasting; Digital communications